The Influence of Brand Ambassador, Brand Image, and Brand Awareness on Decisions to Purchase Skincare - Ariany, Eka; Wangdra, Yvonne (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This research aims to analyze the influence of Brand Ambassador, Brand Image, and Brand Awareness on purchasing decisions for Skintific skincare products in Batam City. In the highly competitive skin care industry, these factors are believed to influence consumers' decisions to purchase products. The method used in this research is a quantitative approach with a survey design, where data is collected through questionnaires distributed to 385 respondents who are Skintific consumers in Batam City. Data analysis was carried out using the multiple linear regression method to test the relationship between the independent variables (Brand Ambassador, Brand Image and Brand Awareness) and the dependent variable (Purchase Decision). The research results show that Brand Ambassador, Brand Image, and Brand Awareness have a significant positive influence on purchasing decisions for Skintific products. Among these three factors, Brand Ambassador shows the greatest influence on purchasing decisions. This research also found that Brand Image and Brand Awareness play an important role in shaping consumer perceptions and increasing intentions to purchase Skintific skincare products. Based on these findings, it is recommended that Skintific strengthen their marketing strategy by selecting relevant brand ambassadors, strengthening a positive brand image, and increasing brand awareness among consumers through various marketing channels.